A arquitectura na construção do comum - Ana Alexandra Carvalho Pinheiro (2017)
The present dissertation as a moment that anticipates the professional activity is approachedas an opportunity to reflect on the social role of the architect where, very briefly, it is intendedthat works, authors and personal projects serve as a reflection of this responsibility.The dissertation evolves on about alternative ways of doing architecture; ways that helpbuilding a less alienated and repressive society, translated into a space of dialogue, open andavailable. Throughout the examples, the role of the architect, the reach and the ability of theprofession to follow cultural commitments are reflected; to contribute to the production ofenvironments that give humanity the conditions of community life. This possibility is a purposefor the architect-me project which is called "common construction".The uncertainty about the existence of a common project / ideal or the possibility of a socialrole of the architect these days is fed by authors who describe the same anguish. The time andknowledge of other names appeases the doubts when finding them answers. That said, thechallenge of this work is to weave the anguishes and consolations, questions and answers -unambiguously articulate, but the "how" was never an easy evidence.